Design of an Integrated Database System for Optimizing Laundry Services - Geasela, Yemima Monica; Leonardy, Randy Frederick; Reynald, Andreanus Joe; Jonatan, Dantacitto (Universitas Bunda Mulia, 2025)
The rapid advancement of technology has brought significant changes across various sectors, including service industries like laundry. Many laundry businesses still rely on manual, paper-based record-keeping, which is prone to errors, data loss, and inefficiencies in information retrieval. This traditional method also makes it difficult for business owners to monitor transactions and manage customers effectively. Therefore, this study aims to design a database system that can manage laundry transactions more efficiently, accurately, and structurally. The research methodology includes direct observation of laundry operations and a literature review on database systems. The database design process consists of three main stages: conceptual, logical, and physical. In the conceptual stage, key entities such as customers, employees, services, transactions, and memberships are identified. The logical stage implements relational schemas using an Entity-Relationship Diagram (ERD) to ensure entity relationships and eliminate data redundancy. The physical stage involves implementing the database design into a Database Management System (DBMS) and testing through anomaly scenarios in insertion, deletion, and updates to ensure data integrity and consistency. The study results indicate that the designed database system enhances laundry operational efficiency by providing more accurate transaction records, faster data retrieval, and improved data security. The use of constraints in the database helps maintain data validity, reduce duplication risks, and improve system reliability in transaction management. With this system, laundry business owners can easily monitor business activities, enhance service quality, and optimize marketing strategies based on customer data. By implementing a structured database system, laundry businesses are expected to adapt to technological advancements, increase competitiveness, and provide more professional services to customers.